An exploratory analysis on the risk to be offended on the internet - Susanne Kirchner; Leopold Sögner (Institute for Advanced Studies (IHS), 2016)
Questionnaire data is used to identify socio-demographic as well as the risk-awareness characteristics of users offended on the Internet. The data comprises a representative sample of 3,000 individuals, containing information on employment, education, age, the frequency of Internet usage and security measures taken by the users. By means of a cluster analysis, within the sub-sample of offended users, we identify a female group, where employment and education are high, a male cluster with similar characteristics, a group of urban users with low security awareness and a group of young users. Regressions show that the frequency of using the Internet increases, while to communicate only to people known in real life reduces the risk to be offended on the Internet.
Keywords: 330; Cyber-Crime; Cluster Analysis; Internet Victimization